Interaction of kidney proteins of normal and hypertensive rats with fragments of renalase peptide RP220 - Buneeva, O A; Fedchenko, V I; Kaloshina, S A; Zavyalova, M G; Zgoda, V G; Medvedev, A E (Biomeditsinskaia khimiia, 2025)
Renalase (RNLS) is a protein involved in the regulation of blood pressure; it has various functions inside and outside cells. The twenty-membered peptide RP220, corresponding to the amino acid sequence of human RNLS 220-239, reproduces a number of effects of extracellular RNLS and can bind to many intracellular proteins in the kidney. The RP220 sequence contains several cleavage sites for extracellular proteases, which could potentially produce RP224-232 and RP233-239 peptides. The aim of this work was to perform proteomic profiling of kidney tissue from normotensive Wistar Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) derived from WKY, using potential proteolytic fragments (RP224-232 and RP233-239) of the RP220 peptide as affinity ligands, and to compare these proteomic profiles with the profiles obtained using the parent RP220 peptide. The obtained results indicate that the relative content of proteins bound to the RNLS peptides in SHR, compared to that in WKY rats, changes most significantly in the case of the RP224-232 peptide. Almost all of these proteins, with a few exceptions, are associated with cardiovascular pathology, many with hypertension. The results of our work indicate that proteolytic processing of RP220 does not lead to the inactivation of this peptide, but to a change in its ligand/regulatory properties, as well as the repertoire of potential protein partners and, consequently, protein-protein interactions that may have possible pharmacological application.